Molecular Phylogeny of Dermacentor parumapertus (Acari: Ixodidae) from Two Locations Within Its Geographical Range. Issue 4 (5th April 2019) - Portugal, J Santos; Allerdice, Michelle; Moraru, Gail M; King, Jonas; Paddock, Christopher D; Becker, Tom; Smith, Travis C; Goddard, Jerome
Abstract: Dermacentor parumapertus Neumann (Acari: Ixodidae) is a rather obscure tick found on jackrabbits in the western United States and parts of Canada and Mexico. Specimens from the northern part of their range are consistently different morphologically from ones found in southern and eastern parts of their range (particularly west Texas), leading some researchers to declare the southern form a variety or subspecies. This study examined field-collected adult D. parumapertus from two main locations—Utah and Texas—within its geographic distribution to ascertain the degree of genetic divergence in the two populations based upon both nuclear and mitochondrial DNA sequences. In total, 30 D. parumapertus were analyzed by PCR using both mtDNA and nDNA genes, and one D. nitens was included for comparison. Trees were constructed for all mtDNA genes individually, as well as after concatenating mtDNA (COI, COII, 12S) and nDNA (2 ITS2 primers), respectively. All constructed trees were exported to FigTree v1.4.3 and TreeGraph v2.14.1–771 beta for visualization. The majority of the Utah and Texas populations of D. parumapertus separated molecularly in both mtDNA and nDNA trees; however, analysis with mtDNA genes showed that 3/13 (23%) of Utah tick specimens were removed molecularly from other specimens collected at the same location. Thus, there was not enough evidence to declare these two disparate and morphologically different populations as distinct and separate species.